1995
DOI: 10.1111/j.1574-6941.1995.tb00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Autecology of a genetically modified fluorescent pseudomonad on sugar beet

Abstract: The survival, dispersal and impact of a genetically modified microorganism (GMM) in the phyllosphere of glasshouse grown sugar beet was investigated. The GMM, Pseudomonas fluorescens SBW25EeZY6KX (lacZY and kanr‐xylE) derived from a bacterium originally isolated from field grown sugar beet, was introduced as a seed inoculum. It survived in the phyllosphere throughout the 531‐day study on plants growing in field soil. The bacterium was highly competitive, in some samples representing the largest bacterial popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The wheat plant yield was significantly negatively impacted by the presence of SBW25 on healthy plants. Strain SBW25 was originally isolated from the sugar beet phyllosphere (Thompson et al, 1995) and later inoculated onto wheat plants in several greenhouse and field studies. In previous studies, it was shown that SBW25 readily colonizes roots, shoots and seeds of wheat (Unge & Jansson, 2001;Jäderlund et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The wheat plant yield was significantly negatively impacted by the presence of SBW25 on healthy plants. Strain SBW25 was originally isolated from the sugar beet phyllosphere (Thompson et al, 1995) and later inoculated onto wheat plants in several greenhouse and field studies. In previous studies, it was shown that SBW25 readily colonizes roots, shoots and seeds of wheat (Unge & Jansson, 2001;Jäderlund et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial PGPR included in this study were P. fluorescens SBW25 (Thompson et al, 1995) andP. brasilensis PB177 (von der Weid et al, 2002).…”
Section: Microbial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies report survival for over 531 days of a genetically modified Pseudomonas fluorescens on sugarbeet leaves in a greenhouse (Thompson et al 1995a(Thompson et al , 1995b. However, the presence of a positive signal, as well as the insecticidal effect remaining on branches, does not necessarily translate in to corresponding survival of the strain released, as the first phenomenon also may be due to its remaining DNA, and the second to the persisting Cry9a toxin crystals.…”
Section: Resultsmentioning
confidence: 93%
“…Pseudomonas fluorescens SBW25 was isolated in 1989 from the phyllosphere of sugar beet in the United Kingdom (Thompson et al, 1995a). This bacterium is an effective colonizer of the rhizosphere and phyllosphere of a number of different plants such as cornflower, pea and wheat (Thompson et al, 1995a, b).…”
Section: Introductionmentioning
confidence: 99%